The historiography workshop: experiences, routes and convergent proposals between Colombia and the Río de la Plata (2023)
The article presents three methodological perspectives to undertake innovative historiographical research. Starting from the metaphor of the workshop, the authors reconstruct part of their trajectory as historians of history. In the first place, an approximation to the world of printed matter on historical issues published in the Colombian 19th century is made from a perspective that combines concern for materials, formats and genres. Then, elements are proposed that seek to put intellectual history and the history of written culture in dialogue as heuristic and analytical references to think about a historiography beyond textual analysis. Finally, based on the case of the Río de la Plata, a series of arguments are presented to get out of the nationalist corset and highlight the relevance of a transnational approach to historiography. The text provides elements for a collaborative agenda that decisively integrates into historiography the contributions of other subdisciplines of history.